Cell differentiation and aging accompanied by depletion of the ACE2 protein - Bártová, Eva; Legartová, Soňa; Krejčí, Jana; Arcidiacono, Orazio Angelo (Aging, 2020)
ACE2 was observed as the cell surface receptor of the SARS-CoV-2 virus. Interestingly, we also found ACE2 positivity inside the cell nucleus. The ACE2 levels changed during cell differentiation and aging and varied in distinct cell types. We observed ACE2 depletion in the aortas of aging female mice, similarly, the aging caused ACE2 decrease in the kidneys. Compared with that in the heart, brain and kidneys, the ACE2 level was the lowest in the mouse lungs. In mice exposed to nicotine, ACE2 was not changed in olfactory bulbs but in the lungs, ACE2 was upregulated in females and downregulated in males. These observations indicate the distinct gender-dependent properties of ACE2. Differentiation into enterocytes, and cardiomyocytes, caused ACE2 depletion. The cardiomyogenesis was accompanied by renin upregulation, delayed in HDAC1-depleted cells. In contrast, vitamin D2 decreased the renin level while ACE2 was upregulated. Together, the ACE2 level is high in non-differentiated cells. This protein is more abundant in the tissues of mouse embryos and young mice in comparison with older animals. Mostly, downregulation of ACE2 is accompanied by renin upregulation. Thus, the pathophysiology of COVID-19 disease should be further studied not only by considering the ACE2 level but also the whole renin-angiotensin system.
Keywords: buněčná diferenciace; Sex Factors; pandemie; angiotensin-konvertující enzym 2; Humans; renin; regulace genové exprese; embryonic heart; buňky HT-29; human kidney embryonic cells; Female; Pandemics; A549 Cells; stárnutí; věkové faktory; HT29 Cells; lidé; HEK293 Cells; zvířata; Angiotensin-Converting Enzyme 2; myši; Aging; Mice; sexuální faktory; Renin; ACE2; COVID-19; ženské pohlaví; Gene Expression Regulation; Male; HEK293 buňky; Cell Differentiation; Age Factors; Animals; lung cancer cells; buňky A549; mužské pohlaví; SARS-CoV-2; Renin-Angiotensin System; renin-angiotensin systém